2018
DOI: 10.1007/s11356-018-2616-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus subtilis and nanohydroxyapatite on the metal accumulation and microbial diversity of rapeseed (Brassica campestris L.) for the remediation of cadmium-contaminated soil

Abstract: This study investigated the effects of the co-application of Bacillus subtilis and nanohydroxyapatite (NHAP) on plant growth, soil cadmium (Cd) dynamics, and the microbiological characteristics (such as enzyme activity and bacterial species richness) of the rhizosphere soil. Rapeseed was used as a model plant in pot experiments. Different concentrations of B. subtilis and 0.5% NHAP were applied alone and in combination to Cd-contaminated soil. The Cd contents in soils and plants as well as the rhizospheric mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…It can be used as a potent geomicrobiological stabilizer for immobilization of Pb, Sb, Ni, Cu and Zn in alkaline soils. The application of nanohydroxyapatite (NHAP) along with B. subtilis to cadmium contaminated soil improved soil remediation and increased rhizospheric community (Liu et al, 2018). UV-mutated species B. subtilis 38, served as an efficient sorbent of Hg, Cr, Cd and Pb (Wang et al, 2019).…”
Section: Bioremediation Of Pollutantsmentioning
confidence: 99%
“…It can be used as a potent geomicrobiological stabilizer for immobilization of Pb, Sb, Ni, Cu and Zn in alkaline soils. The application of nanohydroxyapatite (NHAP) along with B. subtilis to cadmium contaminated soil improved soil remediation and increased rhizospheric community (Liu et al, 2018). UV-mutated species B. subtilis 38, served as an efficient sorbent of Hg, Cr, Cd and Pb (Wang et al, 2019).…”
Section: Bioremediation Of Pollutantsmentioning
confidence: 99%
“…The triumphant elimination of Cd in Cd-polluted water illustrated the competence of Pseudomonas aeruginosa improved Cd bioreduction which in turn hasten the cadmium sulfide (CdS) NPs biosynthesis (Raj et al, 2016). Likewise, the removal and bioremediation of Cd from Cd-polluted soils also evaluated (Liu et al, 2018b). The authors demonstrated that the co-treatment of Bacillus subtilis and nano-hydroxyapetite (NHAP) efficiently eliminated the Cd contamination, encouraging the propagation of microbial community of rhizosphere along with the diversity of bacteria in the remediated soil (Liu et al, 2018b).…”
Section: Heavy Metalsmentioning
confidence: 99%
“…Likewise, the removal and bioremediation of Cd from Cd-polluted soils also evaluated (Liu et al, 2018b). The authors demonstrated that the co-treatment of Bacillus subtilis and nano-hydroxyapetite (NHAP) efficiently eliminated the Cd contamination, encouraging the propagation of microbial community of rhizosphere along with the diversity of bacteria in the remediated soil (Liu et al, 2018b). The evaluation of somewhat variable biofunctionalized approach including polyvinylpyrrolidone (PVP)coated iron oxide NPs intermingled with Halomonas sp.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…Biofunctionalization of metallic nanoparticles >90% removal rate [50] Cadmium Bacillus subtilis Biofunctionalization of Nanohydroxyapatite 43.15%-57.04% increased removal efficiency than that of control [51] heavy metals on a solid surface and achieving stabilized state when the concentration of heavy metal is adsorbed. However, along with such positive sides, it also has some limitations like low efficiency and sorption capacities.…”
Section: Escherichia Colimentioning
confidence: 99%